The missus ebook - James, E L. (Mister & Missus, 2023)
The follow-up to the #1 New York Times bestseller, The Mister, a passionate and thrilling love story from E L James, author of the phenomenal bestselling Fifty Shades Trilogies. Alessia regards her husband through heavy-lidded eyes. You'll have to fight for him. Her mother's words from their call this morning ring through her head. And fight, she will. Using every available weapon she has. She loves him. She knows this. She wants him. And she wants him to want her. What happens once the glass slipper fits...? Maxim Trevelyan, reluctant Earl of Trevethick, has pursued the woman he loves to the wilds of Albania. Having fought for and won her, he now has to wed her, at the sharp end of a shotgun. But can a reformed rake like Maxim ever make a good husband — or will his own notorious reputation and the scandalous secrets of his aristocratic family destroy his newfound happiness? Alessia Demachi has defied and outwitted kidnappers and traffickers, and won the heart of the man she loves, but can she make this marriage work? Confronted by Maxim's lurid past, his forbidding family, and the looks and whispers of London's elite, will she ever be seen as Maxim's countess — or will she always be his former cleaner? From the majestic mountains of Albania, through the rural idyll of the English countryside, to the shady glamour of contemporary London, The Missus is a spellbinding journey of love, longing, acceptance, and redemption.